Death and the author - Ellis, David (Oxford University Press, 2008)
Organized around a dramatic account of D.H. Lawrence's desperate struggle against tuberculosis, and of the bizarre events which followed his death, this text offers a series of often grimly humorous reflections on death and dying.
10.1093/acprof:oso/9780199546657.001.0001
Keywords: Lawrence; D. H; Authors